2011
DOI: 10.1186/1472-6882-11-91
|View full text |Cite
|
Sign up to set email alerts
|

Black tea extract prevents lipopolysaccharide-induced NF-κB signaling and attenuates dextran sulfate sodium-induced experimental colitis

Abstract: BackgroundBlack tea has been shown to elicit anti-oxidant, anti-carcinogenic, anti-inflammatory and anti-mutagenic properties. In this study, we investigated the impact of black tea extract (BTE) on lipopolysaccharide (LPS)-induced NF-κB signaling in bone marrow derived-macrophages (BMM) and determined the therapeutic efficacy of this extract on colon inflammation.MethodsThe effect of BTE on LPS-induced NF-κB signaling and pro-inflammatory gene expression was evaluated by RT-PCR, Western blotting, immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The extracts of tea and cocoa had noticeable anti‐inflammatory functions (Song et al . ; Khan et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts of tea and cocoa had noticeable anti‐inflammatory functions (Song et al . ; Khan et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Catechins are abundant flavonoids in tea and cocoa. The extracts of tea and cocoa had noticeable anti-inflammatory functions (Song et al 2011;Khan et al 2014). The EGCG is the most widely studied catechin for its anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…To model human IBD, a DSS‐induced mouse model was setup and has been used for evaluation of potential medications. DSS is directly cytotoxic to enterocytes of the basal crypts and leads to breakdown of intestinal barrier integrity, translocation of enteric microbiota and induction of colitis (Song et al ., ). In this study, all of the mice administrating with DSS showed body weight loss, colon swelling and shortening.…”
Section: Discussionmentioning
confidence: 97%
“…Like NO and PGE 2 produced by iNOS and COX-2, respectively, the release of pro-inflammatory cytokines is regulated by NF-κB pathway and plays an important role in the induction of the innate immune response of the acquired immune response [23]. It has been well studied that the inhibition of NF-κB activation by black tea extract is associated with the phosphorylation, ubiquitination, and subsequent degradation of IκB via ubiquitin-proteosome pathway [24]. Although biochemical actions of EMM on NF-κB regulations remain unknown, the present study showed that EMM potentially inhibits the proteolytic degradation of IκB-α and the NF-κB promoter-driven luciferase expression induced by LPS in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%